Cyclic isoDGR and RGD Peptidomimetics Containing Bifunctional Diketopiperazine Scaffolds are Integrin Antagonists. Issue 16 (11th March 2015) - Panzeri, Silvia; Zanella, Simone; Arosio, Daniela; Vahdati, Leila; Dal Corso, Alberto; Pignataro, Luca; Paolillo, Mayra; Schinelli, Sergio; Belvisi, Laura; Gennari, Cesare; Piarulli, Umberto
Abstract The cyclo[DKP‐isoDGR] peptidomimetics 2–5, containing bifunctional diketopiperazine (DKP) scaffolds that differ in the configuration of the two DKP stereocenters and in the substitution at the DKP nitrogen atoms, were prepared and examined in vitro in competitive binding assays with purified αvβ3 and αvβ5 integrin receptors. IC50 values ranged from low nanomolar (ligand 3) to submicromolar with αvβ3 integrin. The biological activities of ligands cyclo[DKP3‐RGD] 1 and cyclo[DKP3‐isoDGR] 3, bearing the same bifunctional DKP scaffold and showing similar αVβ3 integrin binding values, were compared in terms of their cellular effects in human U373 glioblastoma cells. Compounds 1 and 3 displayed overlapping inhibitory effects on the FAK/Akt integrin activated transduction pathway and on integrin‐mediated cell infiltration processes, and qualify therefore, despite the different RGD and isoDGR sequences, as integrin antagonists. Both compounds induced apoptosis in glioma cells after 72 hour treatment.